Identification of circumferential pulmonary vein isolation responders among patients with persistent atrial fibrillation: clinical value of the sequential low-dose ibutilide test. Issue 8 (8th June 2020) - He, Shu-Nan; Tian, Ying; Shi, Liang; Wang, Yan-Jiang; Xie, Bo-Qia; Li, Xue-Xun; Zeng, Li-Jun; Yang, Xin-Chun; Liu, Xing-Peng
Abstract: Aims: Circumferential pulmonary vein isolation can be effective as sole treatment for persistent atrial fibrillation. However, identifying those patients who will respond to this therapy remains a challenge. We investigated the clinical value of the sequential low-dose ibutilide test for identifying patients with persistent atrial fibrillation in whom pulmonary vein isolation is effective as sole therapy. Methods and results: In a prospective cohort of 180 consecutive patients with persistent atrial fibrillation, intravenous low-dose (0.004 mg/kg) ibutilide was administered 3 days before ablation and after the completion of circumferential pulmonary vein isolation. In patients in whom ibutilide did not terminate atrial fibrillation pre-procedurally, but successfully terminated it intraprocedurally, no further atrial substrate modification was performed. Pre-procedural low-dose ibutilide failed to terminate the arrhythmia in all patients with persistent atrial fibrillation, while pulmonary vein isolation ± low-dose ibutilide terminated persistent atrial fibrillation in 55 (30.6%) of them (PsAF group 1). The remaining 125 (69.4%) patients underwent electrogram-based ablation (PsAF Group 2). The control group comprised 379 consecutive patients with paroxysmal atrial fibrillation who underwent pulmonary vein isolation over the same period. At 24 months follow-up, 39 (70.9%) patients in PsAF Group 1 and 276 (72.8%) patients in the control group were free from atrial tachyarrhythmias ( P = NS); the arrhythmia-free rates in both groups were higher than that in PsAF group 2 (58.4%, P  = 0.005). Conclusion: The sequential low-dose ibutilide test is a simple method for identifying patients with persistent atrial fibrillation in whom pulmonary vein isolation alone is an appropriate treatment strategy.